Designing with microbial cellulose to feed new biological cycles. (1st October 2019) - Cohen, Nitzan; Sicher, Emma; Uğur Yavuz, Seçil
Waste from food packaging and food processing raises a broad scope of critical questions to the food industry revolving around effects to man, nature and society. Reacting on this reality, designers are getting more and more involved as catalysers of innovative and interdisciplinary research by generating alternative proposals and scenarios for more sustainable futures. One of the emerging biodesign fields tackling this issue is growing design, in which organisms such as bacteria, fungi or algae enable the development of more eco-compatible processes and products. Fermentation is an ancient microbial process widely used by food producers. One such fermentation process commonly used to brew Kombucha tea is simultaneously generating microbial cellulose (MC) growing from a symbiotic culture of bacteria and yeasts (SCOBY). In this process, waste coming from food production can be used as nourishment to feed the culture, transforming it into valuable substances. This article addresses an ongoing research project 'InnoCell', a follow-up of 'From Peel To Peel', a design project investigating the fermentation of fruit and vegetable scraps to nourish SCOBY cultures in order to obtain both a beverage (Kombucha tea) and a promising material source (MC). The article highlights the innovative potential of an edible, non-edible and compostable material, proposing alternative biological cycles and speculative future scenarios.